Severity Degrees of Syntropic Stable Arterial Hypotension in the Cirrhotic Patients and Their Dependence on the Daily Blood Pressure Monitoring and Liver Damage Class by C.G. Child – R.N. Pugh - Abrahamovych M.; Farmaha M.; Abrahamovych O.; Fayura O.; Drobinska N. (Львівський клінічний вісник)
Introduction. Daily monitoring of the arterial blood pressure in the cirrhotic patients is used in the practical medicine, as well as in numerous scientific studies for the study of the pathogenesis, clinical and instrumental manifestations of the circulatory system injury. Daily monitoring of the arterial blood pressure should also be used for the syntropic arterial hypotension severity degrees gradation inthe cirrhotic patients. The aim of the study. To determine the syntropic arterial hypotension severity degrees in the cirrhotic patients, their dependence on the daily blood pressure monitoring and liver injury class according to C.G. Child – R. N. Pugh. Materials and methods. The study involved 603 patients with liver cirrhosis (445 men and 158 women, mean age – 48.4 ± 10.3 years), among which – 173 patients with syntropic arterial hypotension, 89 patients of which – with syntropic arterial hypotension without any other disorders of the circulatory system (experimental group). The control group included 26 practically healthy volunteers of the respective gender and age. The daily blood pressure monitoring using the ABPM-04 (Meditech, Hungary) device according to the standard procedure was conducted for all the patients, in addition to the usual examination procedure. Results. It was found that the average, maximum and minimum daily systolic, diastolic, mean and pulse blood pressure, as well as their derivative parameters in the patients of the experimental group, compared with their values in the practically healthy volunteers, are significantly lower, which confirms the presence of stable arterial hypotension in such category of patients. The disorders of the circadian rhythm and blood pressure variability were also found in the patients of the experimental group. The average daily blood pressure is advisable to use to determine the severity of hypotension. In case if the average daily blood pressure, determined by the method of daily monitoring, ranges from 80 mmHg to 76 mmHg, we diagnose mild (I) degree of hypotension, from 75 mmHg to 70 mmHg – the average (II), and in cases when the average daily blood pressure is less than 70 mm Hg -severe (III) degree of arterial hypotension. Among the examined patients (173 patients with arterial hypotension), 54 patients with I degree (31.21 %), 66 patients with II (38.15 %) and 53 patients with III (30.64 %) degree of arterial hypotension were found. The study of correlation between the indicators of daily blood pressure monitoring, depending on the arterial hypotension severity, showed that the average daily blood pressure is the most informative parameter, also the number of some other indicators are informative. After analyzing the distribution of degrees of arterial hypotension, depending on the severity of livercirrhosis by C.G. Child and R.N. Pugh, we found that with the increase of the class, the number of patients with mild (I degree) hypotension decreases and the number of patients with secondary (II degree) and severe (III degree) arterial hypotension increases. Conclusions. We characterized the arterial pressure, recorded by the method of daily blood pressure monitoring. It was found that in the cirrhotic patients there is a syntropic stable arterial hypotension with the disturbed circadian rhythms and arterial pressure variability. The average daily blood pressure is set as the most informative parameter, and the syntropic hypotension is classified into three degrees of severity. Correlative relationships between the parameters of daily blood pressure monitoring and degrees of severity of stable arterial hypotension, among which the strongest has an average daily blood pressure, are revealed. It was stated that with the increase of the liver cirrhosisseverity class by C. G. Child and R. N. Pugh, the number of patients with mild degree syntropic hypotension decreases and the number of patients with syntropic arterial hypotension of moderate andsevere degrees increases.